Jurgis Bielinis – „król przemytników książek”. Przyczynek do badań nad litewskim odrodzeniem narodowym w II połowie xix wieku - Niemojewski, Marcin (Przegląd Środkowo-Wschodni, 2022)
The article is an attempt to outline the profile of Jurgis Bielinis (1846–1918), a Lithuanian book smuggler, publisher and collaborator of the illegal press during the period of the prohibition of printing in Latin, introduced in Lithuania by the Russian administration after the fall of the January Uprising and in force until 1904. The main goal of the article, however, is not a biographical reconstruction, but a search for an answer to the question about the place of Jurgis Bielinis in the multidimensional process of forming a modern Lithuanian nation at the turn of the 19th and 20th centuries, known as the Lithuanian national revival. This goal is to be achieved by examining how this character was written about in Polish and Lithuanian literature on the subject, especially in Lithuanian writings at the end of the 19th century and the interwar period, when the image of Bielinis as a national hero was shaped and preserved in Lithuanian collective memory.